Geochemistry at DSDP Site 76-533 - Matsumoto, R (Supplement to: Matsumoto, R (1983): Mineralogy and geochemistry of carbonate diagenesis of the Pliocene and Pleistocene hemipelagic mud on the Blake Outer Ridge, Site 533, Leg 76. In: Sheridan, RE; Gradstein, FM; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 76, 411-427, https://doi.org/10.2973/dsdp.proc.76.111.1983, 1983)
Bulk X-ray mineralogy of 47 hemipelagic mud and clay samples from the Blake Outer Ridge has revealed that the sediments contain low magnesian calcite, calcian dolomite, ferroan dolomite, and magnesian siderite. Dolomite and siderite are authigenic and occur as rhombohedrons scattered through the sediments, whereas calcite is mostly biogenic. Pliocene dolomitic lenses are made up of interlocking polyhedral grains of ferroan dolomite. The contents of authigenic dolomite and siderite are 3 to 8% in carbonate sediments and 70 to 89% in dolomitic lenses. Dolomite occurs largely in the cores above 192 m sub-bottom depth, whereas siderite occurs in the cores below 87 m. The distribution and occurrence of dolomite and siderite have determined the diagenetic zonation of carbonates as Zone I (dolomitic zone, top-90 m), Zone II (transition zone, 90-180 m), and Zone III (sideritic zone, 180 m-bottom). Measurements of major and minor elements in the untreated total sediment samples and the insoluble residues after digestion in acid-reducing solution have revealed that the soluble fraction concentrates carbonates and ferromanganese associations (Ca, Mg, Sr, Fe, and Mn). Typical "hydrogenous elements" (Co, Cu, Ni, and V) are more concentrated in the insoluble residues rather than in the soluble fraction; the concentrations of these four elements are low and comparable to modern offshore mud, probably because the Site 533 sediments were deposited at a high rate of sedimentation. The contents of Fe2O3 and MnO are somewhat high for rapidly accumulated mud, particularly in the Pliocene sediments (8.09 and 0.26%, respectively, on a Carbonate-free basis). The high Fe and Mn contents are mainly due to the high contribution of the leacheable nonlithogenous fraction; leacheable Fe and Mn originate in the ferromanganese oxide accumulated on the seafloor. Only a small amount of ferric oxide was converted to iron sulfide in the surficial part of Zone I. Most ferromanganese oxide was reduced and precipitated as ferroan dolomite and magnesian siderite in Zones II and III under high alkalinity and high pH conditions in the organic-matter-rich sediments. Fe2+ and Mn2+ in the deeper sediments beneath Zone III possibly migrated upward and concentrated as siderite in Zone III, hence resulting in high contents of Fe and Mn in the Pliocene sediments. Analysis of carbonate zonation on the Blake Outer Ridge has revealed that the zonation is subparallel to the bedding plane rather than to the present seafloor. The sediments at Site 103 on the flank region of the Ridge are lacking Zone I and most of Zone II, probably the result of erosion of the most of the Pleistocene and Pliocene sediments by the enhanced bottom currents during the Pleistocene.